De-blurring Textual Document Images - Oliveira, Daniel M.; Lins, Rafael Dueire; Silva, Gabriel P.; Fan, Jian; Thielo, Marcelo (Graphics Recognition. New Trends and Challenges, 2013)
Document images may exhibit some blurred areas due to a wide number of reasons ranging from digitalization, filtering or even storage problems. Most de-blurring algorithms are hard to implement, slow, and often try to be general, attempting to remove the blur in any kind of image. In the case of text document images, the transition between characters and the paper background has a high contrast. With that in mind, a new algorithm is proposed for de-blurring of textual documents; there is no need to estimate the PSF and the filter proposed can be directed applied to the image. The presented algorithm reached an improvement rate of 17.08% in the SSIM metric.